Uwarunkowania procesów innowacyjnych w Wielkopolsce - Kamiński, Ryszard; Mizgajska, Hanna (Wydział Prawa i Administracji UAM, 1992)
In the 1990s, along the change in the system of functioning of the Polish economy a way of functioning of innovative mechanism has also been changed. Unfortunately, the market system had no impact on the increase of interest in technical progress. To the contrary; regress in that sphere has been noted. It has been caused i.a. by macroeconomic factors. The State policy, oriented at fighting inflation, creating the market, strengthening domestic currency, combined with the inefficient economy unable to adapt to the requirements of the market has resulted in deep recession. It proves that enterprises are unable to adapt to changed circumstances; one of the reasons for such a situation is insufficient innovative capacity. Some causes of regress in innovativeness of the economy are of microeconomica1 nature. Among such factors the most detrimental is the shortage of money for developmental ventures. Among the determinants of technical progress one should mention organizational, legal and informational infrastructure. Despite the fact that in Wielkopolska region the infrastructure is well grounded and diversified, it is insufficient in view of economic requirements.
Conditioning of innovative processes in Wielkopolska region